(untitled) (Journal of Asian Development Studies, 2013)
The present research was conducted to find out the effects of psychological interventions on immune parameters and quality of life in cancer patients. Thirty cancer patients selected from MINAR cancer unit were randomly assign to either an intervention group (n=15) or a control group (n=15). Intervention group patients received weekly group Cognitive Behavior Therapy (CBT) session along with Progressive Muscular Relaxation Training (PMRT) for six weeks. Patients were assessed by Complete blood count test (WBC Differential) and WHOQOL-BREF scale (The WHOQOL Group, 1998) at baseline, after six weeks and one month post study. One way ANOVA and Paired sample t-test were used to analyze the data. Results showed that at base line assessment there were non-significant mean differences in demographics, clinical characteristics, immune parameters and quality of life scores. After six weeks interventions and one month post study there were no significant mean difference found in immune parameter (WBCs, Lymphocytes, Monocytes, Granulocytes and Eosinophils) within group and between groups, however after six weeks interventions and one month post study intervention group patients showed significant greater mean scores in quality of life (Physical Health, Psychological Health, Social relationships and Environment) then control group patients. Findings concludes that psychological interventions are unable to bring any significant change in immune parameters but significantly beneficial for the improvement of quality of life in cancer patients.